Photoelectrochemical Modelling of Semiconducting Electrodes for Neural Interfacing. Issue 2 (1st February 2023) - Chambers, Andre; Prawer, Steven; Ahnood, Arman
Abstract : Semiconducting electrodes are increasingly utilised for neural interfacing applications, such as neural recording, stimulation, and photomodulation. To characterize the performance of these electrodes, photoelectrochemical analysis is often undertaken in biologically relevant electrolytes. These include electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and for photomodulation applications, photocurrent (PC) measurements. From such measurements, it is possible to deduce key properties of semiconductor surfaces, such as electrochemical impedance and capacitance, as well as mechanisms of charge transfer. To extract these parameters from the experimental data, equivalent electrical circuit modelling is often employed, but usually only for a single technique at a time which often misses key insights about the processes occurring at the electrode-electrolyte interface. Here we present an equivalent circuit model that simultaneously describes the results from CV, EIS, and PC transient measurements. Using semiconducting nitrogen-doped ultrananocrystalline diamond (N-UNCD) electrodes in saline solution, we show that the model describes physical mechanisms that occur at the interface with electrolyte, encompassing the space charge region, the electrical double layer, and the electrolyte. Using the model we are able to optimize parameters relevant for neural interfacing and suggest that this framework may assist in the characterization of other semiconducting electrodes.